SEKOLAH PENDIDIKAN PEGAWAI PRIBUMI UNTUK PANGREH PRAJA (OPLEIDING SCHOOL VOOR INLANDSCHE AMBTENAREN-OSVIA) DI SERANG – BANTEN TAHUN 1900 – 1927 - Usmaedi Usmaedi (Diakronika, 2017)
Indigenous School Education Officer for Civil-directed, School Opleiding voor Inlandsche Ambtenaren (OSVIA) in Serang Banten years 1900-1927. This research is based on a system of government that the Dutch East Indies in the program directed by the Government is required to be able to perform administrative tasks in the province but because of the high officials who have to come from the Netherlands to the Dutch government established a school to meet educational officials natives in the province. The purpose of this thesis writers to learn the system of government in the province with the native elite-modern with the traditional school as a condition for becoming a regent. The method that I use the method of Historical done through several stages, namely: (1) Heuristics, (2) criticism, (3) interpretation, (4) Historiography. While the techniques used to obtain data through library research by studying and analyzing various resource books, newspapers, interviews and archival materials related to the issues discussed. The results reveal that the purpose of recruitment administration in Banten just to get the officer natives are very cheap and the Dutch government considers important role for indigenous political elite bureaucracy native is an intermediary between the government and the people using its traditional authority. So the Dutch government established a school to become an administrative officer at the school named Banten OSVIA. After the establishment of the school in Serang Banten OSVIA traditional governance with the pedigree of the king replaced by a modern system which breeds not be the main requirement to be governor, but education has to be provided to the regents, in which a minimum standard of education graduates OSVIA and able to speak Dutch. Thus the author can give lessons to the community and fellow students with thesis title so that I can learn a transitional government would be traditional-modern in Banten after the arrival of the Dutch.